SMART GRIDS WITH GIS TECHNOLOGY - Panyukova, D.V.; Kairanbayeva, A.B.; Nurpeissova, G.B.; Panyukov, K.V. (Academic Scientific Journal of Computer Science, 2020)
Nowadays republican grid in Kazakhstan is regulated to have automated electric power accounting system for every energy supplying entity. However, with wide implementation of units on renewable energy sources (RES), especially in private sector, such measures will not be enough. World scientific community propose a number of methods to modernize grids on national or regional level. One of them is to transit from AC power transmission system to DC power transmission system. It leads to easier connection of plant on RES to the grid and costeffectiveness in power transmission per each kilometer. Other modern approach is real-time digital simulation. Such simulation gives information on grid’s functioning after emergency switching to plan all necessary balancing measures. Next modernization step is in use of phasor measurement units in real-time monitoring for each element of the grid. All of previously specified methods can be developed into GIS on electric power supplement, consumption and transmission. A decentralization on the GIS basis can be implemented to the grid to minimize control delay for the whole system. Authors propose an optimization task for decentralized smart grid on the GIS basis. Such approach allows minimizing reaction time on emergency and power balancing. In addition, it gives opportunity for proper planning of future power construction.